2020
DOI: 10.7759/cureus.8137
|View full text |Cite
|
Sign up to set email alerts
|

Current Management of Paediatric Supracondylar Fractures of the Humerus

Abstract: Supracondylar fractures of the humerus in children are common and can be distressing injuries to the child, the parents and to the surgical team. Type 1 fractures are managed nonoperatively, however displaced fractures (Types 2, 3 and 4) are usually managed surgically. Accurate and repetitive neuromuscular assessment is critical not just for medicolegal reasons but also to expedite management with different specialists if needed. The Rock, paper, scissor, OK technique is simple which is easily understood by mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Furthermore, the assessment using Flynn's criteria showed no significant difference between the outcomes of both treatment groups (p=0.242). [15][16][17][18] Flynn's criteria in the early group showed excellent and good results in 77.2%, and 13.6% cases, respectively, while 10% exhibited poor outcome. Moreover, the corresponding results for the late group were 73.1 %, 15.3% and 11.5% cases.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Furthermore, the assessment using Flynn's criteria showed no significant difference between the outcomes of both treatment groups (p=0.242). [15][16][17][18] Flynn's criteria in the early group showed excellent and good results in 77.2%, and 13.6% cases, respectively, while 10% exhibited poor outcome. Moreover, the corresponding results for the late group were 73.1 %, 15.3% and 11.5% cases.…”
Section: Discussionmentioning
confidence: 91%
“…20 The results showed a nonexistence of non-union cases in both groups, as the distal humerus is an unusual location. 16,17 Therefore, all patients experienced clinical and radiological union within 3 weeks, as well as united fractures at 12 weeks follow-up. These findings are congruent with studies conducted by others, hence open reduction and internal fixation procedure is confirmed not to be a concern for bony union.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Supracondylar humerus fractures are the most common fractures around the elbow in children, constituting 60-65% of all fractures, with a peak incidence between 4 and 7 years of age [1]. According to Gartland's classification and Wilkins Modification of Gartland's classification, types 2b, 3a and 3b are generally treated surgically [2,3]. With the popularization of closed reduction and percutaneous pinning in treating supracondylar humerus fractures, problems such as radiation exposure appear, threatening the patients' and medical staff's health.…”
Section: Introductionmentioning
confidence: 99%
“…3 Supracondylar fractures are classified into extension and flexion types; the extension type is more common accounting for about 97% of the total fractures. 4 This supracondylar region is at higher risk of fracture because of its anatomical structure. It's a thin area connecting the olecranon and coronoid fossae and therefore has higher predisposition to bending forces during fall from height.…”
Section: Introductionmentioning
confidence: 99%